ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PT. MAHAKA MEDIA Tbk PERIODE 2023-2024 - Diva Astrid; Tawakkal (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
This study aims to analyze the financial performance of PT. Mahaka Media Tbk during the 2023–2024 period using a financial ratio analysis approach. The financial ratios applied in this study include liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The data used are secondary data obtained from the company’s annual financial statements published through the Indonesia Stock Exchange. The research method employed is a descriptive quantitative method by comparing the results of financial ratio calculations between periods. The results indicate that the financial performance of PT. Mahaka Media Tbk during the 2023–2024 period experienced fluctuations in several financial ratios. Liquidity ratios reflect the company’s ability to meet short-term obligations, while solvency ratios indicate that the company’s financing structure is still dominated by debt. Profitability ratios show the level of efficiency in generating profits, whereas activity ratios illustrate the effectiveness of the company in managing its assets. Based on the analysis results, it can be concluded that the financial performance of PT. Mahaka Media Tbk during the research period needs improvement, particularly in terms of profitability and asset management efficiency.